Utilization of Activated Rice Husk Powder as a Methyl Orange Dye Adsorbent - Vina Nafidzatul khasanah; Laeli Kurniasari; Indah Riwayati (Journal of Chemical Process and Material Technology, 2023)
Inefficient textile waste processing can pollute the environment and endanger the health of the adjacent community. Methyl orange is one of the most extensively used dyes in the textile industry. Various physical, chemical, and biological processes have been utilized to dispose of methyl orange residue. One of the basics is the adsorption method. This research was conducted to determine the adsorption capacity of activated rice husk powder as an adsorbent to reduce methyl orange content. The activation of rice husk powder also influences the decrease in methyl orange concentrations. The variables used are mass, contact time, and pH, and the adsorption isotherm model is determined. The results demonstrated a decrease in methyl orange concentration from the optimal mass variable of 8 grams, contact time of 60 minutes, and pH of 7, with an adsorption capacity of up to 89%. The adsorption isotherm equation is compatible with the Langmuir equation because the R2 value of 0.926% is closer to 1 than the Freundlich equation.Keywords: Adsorption, Activation, Adsorption Isotherm, Methyl Orange, Rice Husk Powder.